Comprehensive development of industrial symbiosis for the response of greenhouse gases emission mitigation: Challenges and opportunities in China. (March 2017) - Liu, Zhe; Adams, Michelle; Cote, Raymond P.; Geng, Yong; Chen, Qinghua; Liu, Weili; Sun, Lu; Yu, Xiaoman
Abstract: Although not yet a global consensus, there is widespread agreement that climate change is the result of anthropogenic sources of greenhouse gases (GHG) emissions. In order to respond to this issue, society has applied such strategies as clean energy development, improving industrial resource efficiency etc. Despite this, GHG emissions are still pursuing an upward trend. As the largest global GHG emitter, China faces a considerable challenge in responding to its agreed target of 40–45% GHG emission mitigation per unit gross domestic production (GDP) by 2020 as compared to 2005 levels. How to practically achieve this is still largely undecided. Comprehensive development of industrial symbiosis around nationwide is considered part of the solution. However, few researchers have studied how to actually implement a comprehensive development of industrial symbiosis for the purpose of GHG emission mitigation. This work intends to address this gap through highlighting the opportunities to develop such an approach for particular application to GHG emissions reduction in China. In addition, this study will also address the challenges ahead associated with the implementation of such a strategy, and outlines the where future research could be focused. Policy implications like establishing industrial symbiosis indicators associated with GHG emission mitigation are proposed. Highlights: Urgent issue of GHG mitigation and background of industrial symbiosis are introduced. The challenges like lack of indicator, investigating methodologies and regional disparity are analyzed. Opportunities for GHG mitigation through comprehensive development of industrial symbiosis are detailed. Policy implications for responding GHG mitigation through industrial symbiosis are proposed.